2021
DOI: 10.1039/d1fo00113b
|View full text |Cite
|
Sign up to set email alerts
|

Reprogrammed intestinal functions in Astragalus polysaccharide-alleviated osteoporosis: combined analysis of transcriptomics and DNA methylomics demonstrates the significance of the gut–bone axis in treating osteoporosis

Abstract: Researchers have noted that organ-organ communication between the bone and the intestine has significant effects on bone health and its related diseases. In this study, we collected colonic epithelial tissue...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In rats, OS has been demonstrated to cause intestinal dysfunction. Additionally, reprogramming intestinal function through the gut-bone axis, drugs potentially modulate bone metabolism ( 30 , 31 ). By producing metabolites, which enter the systemic circulation from the gastrointestinal tracts, microorganisms were known to have an impact on bone ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, OS has been demonstrated to cause intestinal dysfunction. Additionally, reprogramming intestinal function through the gut-bone axis, drugs potentially modulate bone metabolism ( 30 , 31 ). By producing metabolites, which enter the systemic circulation from the gastrointestinal tracts, microorganisms were known to have an impact on bone ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that APS exerts its anti-inflammatory effect by inhibiting LPS-induced production of TNF-α and IL-8 in intestinal epithelial cells by blocking mitogen-activated protein kinase (MAPK) transcriptional activity (Yuan et al, 2009). In addition to identifying the role of APS through its antiinflammatory and antioxidant properties, recent studies have demonstrated a link between APS and the DNA methylome (Liu et al, 2021). In this study, we verified that APS exerts its antiinflammatory effect on THP-1 macrophages through m 6 A modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of osteoclast differentiation and the calcium signaling pathway might contribute to the improvement of osteoporosis. 116 Other Gut Axis Pathways Involving Prebiotics. Sinha et al introduced the regulation of the intestinal microbiome as a potential adjuvant treatment for certain skin diseases, particularly through studies on oral probiotics, prebiotics, and dietary improvements.…”
Section: Journal Ofmentioning
confidence: 99%
“…APS restored intestinal function in osteoporotic rats by reversing the expression of 53 DEGs. Recovery of osteoclast differentiation and the calcium signaling pathway might contribute to the improvement of osteoporosis …”
Section: Health Benefits Of Prebiotics Through Gut Axis Regulationmentioning
confidence: 99%